Investigating the Correlation between Electrolyte Concentration and Electrochemical Properties of Ionogels - Suen, Ji Wei; Elumalai, Naveen Kumar; Sujan, Debnath; Mubarak, Nabisab Mujawar; Lim, Chye Ing; Mohan Reddy, Moola; Tan, Yee Seng *; Mohammad, Khalid * (MDPI, 2023)
Ionogels are hybrid materials comprising an ionic liquid confined within a polymer matrix. They have garnered significant interest due to their unique properties, such as high ionic conductivity, mechanical stability, and wide electrochemical stability. These properties make ionogels suitable for various applications, including energy storage devices, sensors, and solar cells. However, optimizing the electrochemical performance of ionogels remains a challenge, as the relationship between specific capacitance, ionic conductivity, and electrolyte solution concentration is yet to be fully understood. In this study, we investigate the impact of electrolyte solution concentration on the electrochemical properties of ionogels to identify the correlation for enhanced performance. Our findings demonstrate a clear relationship between the specific capacitance and ionic conductivity of ionogels, which depends on the availability of mobile ions. The reduced number of ions at low electrolyte solution concentrations leads to decreased ionic conductivity and specific capacitance due to the scarcity of a double layer, constraining charge storage capacity. However, at a 31 vol% electrolyte solution concentration, an ample quantity of ions becomes accessible, resulting in increased ionic conductivity and specific capacitance, reaching maximum values of 58 ± 1.48 μS/cm and 45.74 F/g, respectively. Furthermore, the synthesized ionogel demonstrates a wide electrochemical stability of 3.5 V, enabling diverse practical applications. This study provides valuable insights into determining the optimal electrolyte solution concentration for enhancing ionogel electrochemical performance for energy applications. It highlights the impact of ion pairs and aggregates on ion mobility within ionogels, subsequently affecting their resultant electrochemical properties.